The essence of counsellors in the fight against drugs and substance abuse - Mapfunde, Davie; Mukaro, Juliet; Mzizi, Lynn; Mapolisa, Alfred; Chipika, Charles Govero (ARKA INSTITUTE, 2025)
The main thrust of this qualitative case study research was to establish the essence of counsellors in the fight against drug and substance abuse, informed by Beck’s (1960) Cognitive Behavioral Theory. While both convenience and purposive sampling techniques were adopted in the selection of participants, qualitative data gathering instruments namely semi-structured interviews and focus group discussions were used to collect data. A phenomenological analysis (PA) was utilized to analyse the lived experiences and meanings of participants. The study established that counsellors are pivotal in the management and reduction of drug and substance abuse as they adopt counselling and relapse management. They also help in educational circles by ensuring that mental health is stabilised as youths are made to focus on education and development of the economy. To this end, the research recommends that counsellors should foster collaborative relationship and use multidisciplinary approach in addition to staying updated and using a variety of public awareness activities for both abusers and would be abusers. Overall, the study is significant to policy makers and professionals as they will make informed decisions that are research-based.